Sistem Pakar Klasifikasi Permasalahan Berdasar AUM Menggunakan FCM-FIS Tsukamoto - Ainun Najib Eka Christianto; Rekyan Regasari Mardi Putri; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Alat ungkap masalah is an instrument in guidance and counseling are used to discover and understand any problems experienced by students. Alat ungkap masalah is used because of the lack of a deep understanding of teachers' guidance and counseling to students. Although already used alat ungkap masalah student counseling service process is still less than the maximum because of the lack of human resources that exist in schools and teachers' understanding of guidance and counseling about the tool according to the problems and issues faced by the students. Therefore, it is necessary to develop an expert system that can adopt the knowledge of an expert counseling in the process of recognition of the problem by using the tool revealed the problem. The purpose of this application is to help the teachers counseling to ease the process of guidance and counseling and facilitate students in recognizing the problems that it faces. This application uses the FCM Clustering as the generation process and FIS rules Tsukamoto as an inference engine, the application can generate an accuracy rate of 75.71% compared with the results of the expert diagnosis.